A Clinical Study on Obesity in children in Rural Medical College - Kashavoyina Muralidhar; Sarfarz, Mohammad; A Bhaskar (Asian Journal of Clinical Pediatrics and Neonatology, 2021)
Background: Obesity is one of the most common disorders in medical practice and is the most frustrating and difficult to treat condition. Obesity is defined as the excess of adipose tissue. Body fat can be detected by physical examination, but body mass index (BMI) is used for more quantitative evaluation. Overweight and obese are the 5th leading cause of global deaths. In 2008 more than 1.4 billion adults (20 years and older) were overweight. In 2012 more than 40 million children under 5years of age were overweight. Once considered high-income country problem, the overweight and obesity are now rising in low and middle-income countries, particularly in urban settings. Close to 30 million children are living in developing and 10millon in developed countries. Childhood obesity is associated with a higher chance of premature death and disability in adulthood. The aim is to study the pattern of obesity in children in rural medical college. Subjects and Methods: We have conducted this study for 8 months from March 2020 to October 2020 in the department of pediatrics in Kamineni medical college. Informed consent has been taken from parents and the college ethical committee approval has been obtained. careful history taking, height and weight were measured for each child by trained paramedical staff. We have included 965 children in this study. Results: We have included 965 total children in this study out of these 965, boys were 445 and girls were 520. The studied age group is between 8 and 16 years. All are from different residential areas and parents were of different qualifications and occupations. In our study we found the total overweight and obese children were 230. Conclusion: Obesity is a common medical problem in India and worldwide also. It is observed commonly in girls. In rural areas also the prevalence in girls is high. In rural areas, lack of physical activity and faulty eating habits may be common causes for increasing prevalence.